IbM SEKOLAH SMKN 3 DAN SMPN 1 MATTIRO BULU KABUPATEN PINRANG - Harlinda, Harlinda; Kasman, Kasman; Satra, Ramdan (Jurnal BALIRESO, 2017)
School information management system aims to reviewfixing system Information The information in schools as teachers, principals, students, classes, lessons eyes, books, Library and lay forth. Singer information systems will be integrated by internet network will make school all information about the better because can be accessed operating rooms and digital. Schools can be using information whenever and wherever singer for access internet. So also with community orothers singer needs information can be easy access to a system with singer.The school attendance system entered the school information management system hearts can be made implementation class teaching and learning process for the better. Article search google fingerprint attendance system will become moreeasy to review control the presence of students in class so it can be easier for school parties hearts supervise school pupils and maximize school activities. oversight school Indispensable to review reducing negative actions that can be detrimental to parties and parties of school pupils or orangutan parents. Article search google SMS gateway system, the parents role hearts pupils participating supervise school pupils can be done becausewithsystem also singer yang sangat will give information to review helps control functions hearts oversee school activities all school pupils.